Effect of the process parameters on the energy transfer during the synthesis of the 2LiBH4/MgH2 reactive hydride composite for hydrogen storage - Jepsen, Julian (2019)
: Several different milling parameters (additive content, rotation velocity, ball-to-powder ratio, degree of filling, and time) affect the hydrogen absorption and desorption properties of a reactive hydride composite (RHC). In this paper, these effects were thoroughly tested and analyzed. The milling process investigated in such detail was performed on the 2LiH-MgB2 system doped with TiCl3. Applying an upgraded empirical model, the transfer of energy to the material during the milling process was determined. In this way, it is possible to compare the obtained experimental results with those from processes at different scales. In addition, the different milling parameters were evaluated independently according to their individual effect on the transferred energy. Their influence on the reaction kinetics and hydrogen capacity was discussed and the results were correlated to characteristics like particle and crystallite size, specific surface area, presence of nucleation sites and contaminants. Finally, an optimal value for the transferred energy was determined, above which the powder characteristics do not change and therefore the RHC system properties do not further improve.